ETIKA DISTRIBUSI DALAM EKONOMI ISLAM - Tasriani Tasriani; Dessyka Febria (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The purpose of this paper is to produce a description of the ethics of distribution in Islamic economics. This theme is motivated by the Islamic economic system which is an advanced system of the Islamic social system which is expected to provide solutions to various existing problems with policies that favor the benefit and justice of the people's economy. The distribution policy in the Islamic economic system upholds the value of justice which is based on the concept of distribution in the Qur'an so that wealth does not accumulate in only one group.This paper uses a qualitative approach with a descriptive type. Qualitative approach to describe distributional ethical literacy in Islamic economics. Descriptive type to describe in detail the distribution phenomena that occur in marketing contained in various studies.The result of this paper is that the ethical distribution of a marketing intermediary channel in various aspects of goods or services from the hands of producers to consumers by distributing directly, semi-directly and indirectly, in an Islamic-based economic system requires distribution to be based on two values, namely the value of freedom and the value of justice. The phenomenon shows that the ethics of distribution in Islamic economics include having the intention of worship and sincerity, transparency, fairness, mutual assistance, tolerance and alms, not exhibiting goods that cause perceptions, never neglecting worship due to distribution activities, prohibition of Ikhtikar (monopoly), seeking a reasonable profit, etc.